2021
DOI: 10.1007/s13201-021-01481-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of chromium (Cr6+) on dead biomass of Salvinia molesta (Kariba weed) and Typha latifolia (broadleaf cattail): isotherm, kinetic, and thermodynamic study

Abstract: This study evaluated the adsorption of Cr6+ from aqueous solution using dead biomass of aquatic plants Salvinia molesta (Kariba weed) and Typha latifolia (broadleaf cattail). The batch experiments were carried out to study the effects of pH, adsorbent dose, initial metal concentration, contact time, agitation speed in rotation per minute (rpm), and temperature. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to characterize the adsorbent and analyze the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Salvinia minima can remove Cd(II), Pb(II), and Cr(VI) but is affected by environmental conditions such as pH and light intensity [ 34 ]. It has also been shown that dead S. molesta tissue functions as a Cr(VI) adsorbent, with an adsorption capacity of 33.33 mg/g following a Langmuir isotherm model [ 35 ]. Another study showed that after chemical modification of the surface of Salvinia sp., its Cr(VI) adsorption capacity can be improved [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salvinia minima can remove Cd(II), Pb(II), and Cr(VI) but is affected by environmental conditions such as pH and light intensity [ 34 ]. It has also been shown that dead S. molesta tissue functions as a Cr(VI) adsorbent, with an adsorption capacity of 33.33 mg/g following a Langmuir isotherm model [ 35 ]. Another study showed that after chemical modification of the surface of Salvinia sp., its Cr(VI) adsorption capacity can be improved [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chromium is present in several forms in soil, but the well-known and constant forms are Cr(III) and Cr(VI), with Cr(VI) having greater capability of penetrating plant roots [ 2 ]. The hexavalent form, Cr(VI), by entering plant roots, can disrupt crucial cellular structures more than other Cr forms [ 5 , 6 ]. The form Cr(III) is required for humans, while the Cr(VI) form is reported as a human health hazard [ 2 ].…”
Section: Introductionmentioning
confidence: 99%